Fruit Development in Balanites roxburghii Pl. - Amalraj, V. A.; Shankaranarayan, K. A. (Indian Forester, 1995)
Balanites roxburghii fruits are potential alternative source of diosgenin oil and protein. Fruit developmental morphology has been investigated by measuring the rate of growth and studying the internal structure at different perjods of time. Three distinct growth phases were distinguishable. The cause for curvature of young,fruits was found due to the displacement of the four aborted ovules by the developing fertilised ovule. Spray treatment with Gibberelic Acid 200 ppm was found effective in controlling early fruit drop which was heavy.